QUALITATIVE STUDY OF THE ROLES AND CHALLENGES OF EMPLOYEES AT PROGRAM PERKULIAHAN ASIK AS A HIGHER EDUCATION CONSULTING INSTITUTION - Wicaksono, Sakti (BAIK Publishers, 2025)
This qualitative study explores the roles and challenges of employees at Program Perkuliahan ASIK, a higher education consulting institution specializing in flexible learning programs for working adults. Employing purposive sampling, the study involved in-depth interviews with employees performing diverse functions including academic advising, program coordination, administrative facilitation, and stakeholder liaison. Findings reveal that these multifaceted roles significantly contribute to student retention rates exceeding 85% by providing personalized guidance and innovative program design. However, employees face substantial challenges such as high workloads, rapid policy shifts, resource constraints, and balancing diverse stakeholder expectations, which result in stress, role conflicts, and potential burnout. Coping mechanisms involve peer mentoring and informal support, though formal training is limited. The study recommends structured professional development, workload audits, enhanced technology infrastructure, clear role definitions, and supportive organizational cultures to sustain service quality and employee well-being. These insights inform institutional strategies for optimizing human resource management in higher education consulting contexts.